고구마 재배 밭토양에서 가축분퇴비의 시용량이 아산화질소 발생에 미치는 영향 - 김성은; Sung Un Kim; 루앙카르스추안핏; Chuanpit Ruangcharus; 이현호; Hyun Ho Lee; 박혜진; Hye Jin Park; 홍창오; Chang Oh Hong (Hanguk hwangyeong nonghak hoeji, 2018)
BACKGROUND: Composted animal manure applied to the arable soil for improving soil quality and enhancing crop productivity causes greenhouse gas emissions such as nitrous oxide (N 2 O) by processes of nitrification and denitrification. However, little studies have been conducted on determining effect of application ratio of composted animal manure on N 2 O emission rate and its annual emission pattern from upland soil in South Korea. Therefore, this study was conducted to determine N 2 O emission rate and its annual emission pattern from upland soil supporting for sweet potato. METHODS AND RESULTS: Composted animal manure was applied at the ratio of 0, 10, and 20 Mg/ha to an upland soil supporting for sweet potato (Ipomoea batatas). Nitrous oxide emission was examined during growing season and non-growing season from May 2016 through May 2017. Daily N2O fluxes showed peaks right after applications of composted animal manure and inorganic nitrogen fertilizer. Precipitation and soil water content affected daily N2O flux during non-growing season. Especially, N2O flux was strongly associated with water filled pore space (WFPS). We assumed that the majority of N2O measured during growing season of sweet potato was produced from nitrification and subsequent denitrification. Annual cumulative N2O emission rate significantly increased with increasing application ratio of composted animal manure. It increased to 12.0 kg/ha/yr from 8.73 kg/ha/yr at control with 10 Mg/ha of composted animal manure and to 14.0 kg/ha/yr of N 2 O emission with 20 Mg/ha of the manure. CONCLUSION: To reduce N 2 O emission from arable soil, further research on developing management strategy associated with use of the composted animal manure and soil moisture is needed.